INTEGRASI “ILMU DAN AGAMA” SEBAGAI ISLAMISASI ILMU PENGETAHUAN - Albarra Sarbaini; Nanat Fatah Natsir; Erni Haryanti (Ri'ayah: Jurnal Sosial dan Keagamaan, 2022)
The discussion and development of science cannot stand alone, but it is always related to other issues, including religion. On the contrary, the discussion of religion will never be separated from the influences caused by advances in science and technology. From here, the intergration of science and religion becomes important to talk about. The science that essentially studies nature as it is begins to question things of a supposed nature (moral, religious). For example, the question, what exactly should science be used for, Where are the limits of scientific colonization authority, In which direction should scientific development be carried out, These kinds of questions are now important, and to answer them scientists inevitably have to turn to morals and religion. This means that discussions about the integration of science and religion are inevitable.